Pengaruh Status Kebersihan Gigi dan Mulut (OHI-S) Pada Lansia yang Menggunakan Gigi Tiruan Sebagian Lepasan Berdasarkan Jenis Kelamin - Wuri, Puteri Anugerah; Sugiatno, Erwan (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2007)
The goal of the research is to know the inï¬‚uence oral hygiene status (OHI-S) of elderly people wear removable partial denture (RPD) base on gender: RPD is denture to replace one or more tooth, but it is not replace all of the tooth and it can overhaul to the mouth of the user Subject involved I5 man elderly people and 15 women elderly people wear RPD on Umbulharjo Yogyakarta. T he result of OHI-S examination, man have good OHI-S I (3,3%), middle 3 (10%), poor I1 (36, 7%) and woman have OHI-S good 7 (23,3%), middle 5 (16, 7 %) and poor 3 (10%). The result showed that p 0, 05 and get chi-square count (9,571) chi- square table (5,99) with signiï¬cant 0,008, it means have meaning the inï¬‚uence OHIS of elderly people wear RPD base on gender: